Do Parties Matter for Economic Outcomes? A Replication Study of Pettersson-Lidbom (Journal of the European Economic Association, 2008) - Martin Korpi; Erik Lakomaa (Journal of Comments and Replications in Economics (JCRE), 2026)
In an important and much cited study, Pettersson-Lidbom (2008) identifies significant left-wing majority coalition effects on economic outcomes for Swedish local governments, 1974-1994. We first replicate the original study and then extend the original research by applying Pettersson-Lidbom's empirical model using new and more detailed coalition data, compiled from registry books and register data recently made available from Statistics Sweden. The data allows us to test for left party policy outcomes including previously undefined coalitions, such as left minority coalitions and coalitions with local or emerging parties. We find that Pettersson-Lidbom's previous results hold and are even strengthened using the new data and some alternative specifications, but the results are heavily dependent on the definition of left-wing rule. When including left wing minority coalitions and left-wing coalitions including the Green Party, previous significant differences between the left and right are no longer discernable.
https://doi.org/10.15456/j1.2026047.0919846576
Keywords: C21; D72; D78; H71; H72; 330; Democracy; Voting behaviour; Economic policy; Political systems